Justification of Wife Beating in Adolescents: Associated Beliefs and Behaviors. (February 2019) - Devenish, Bethany; Hooley, Merrilyn; Mellor, David
Socioeconomically disadvantaged adolescents who are exposed to social norms related to violence against women are more likely to experience or be perpetrators of intimate partner violence. This study evaluated factors hypothesized to be associated with acceptance of wife beating among 240 male and female adolescents aged 10-16 years participating in a World Vision program in Armenia. Acceptance of wife beating was associated with relational victimization, perceived social support, and parent and community boundaries and expectations, but was not associated with overt victimization or aggression. These findings highlight several areas that may be important for violence prevention research.